Wycena opcji rozszerzenia projektu inwestycyjnego metodą dwukrotnej symulacji Monte Carlo - Wiśniewski, Tomasz (Valuation of Expansion Option with Double Monte Carlo Method, 2007)
The paper examines concept of specific method of real option valuation based on simulation approach. Monte Carlo (MC) simulation is proposed by Copeland and Antikarov to resolve the problem of many uncertainty factors influencing the project. In the next step typical option valuation techniques could be used - MC simulation being one of them. The proposal of the author is to simulate the expected value of the project in two steps. In the first step MC simulation calculates the base value of the project without option and the second MC simulation calculates the expected value of the project with option. To achieve this valuation model used for the second simulation one has to imitate response of the company to changing environment in that way as the real option is actually exercised.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 628-638